2013
DOI: 10.1189/jlb.0413206
|View full text |Cite
|
Sign up to set email alerts
|

Human TLR8 is activated upon recognition ofBorrelia burgdorferiRNA in the phagosome of human monocytes

Abstract: Phagocytosed Borrelia burgdorferi (Bb), the Lyme disease spirochete, induces a robust and complex innate immune response in human monocytes, in which TLR8 cooperates with TLR2 in the induction of NF-κB-mediated cytokine production, whereas TLR8 is solely responsible for transcription of IFN-β through IRF7. We now establish the role of Bb RNA in TLR8-mediated induction of IFN-β. First, using TLR2-transfected HEK.293 cells, which were unable to phagocytose intact Bb, we observed TLR2 activation by lipoprotein-ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
68
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 77 publications
(75 citation statements)
references
References 85 publications
5
68
0
Order By: Relevance
“…Human blood monocytes also sense Borrelia burgdorferi RNA via TLR8, resulting in IFN-b production (43,44). Although this finding is in agreement with our present study on S. aureus, the proposed signaling mechanisms are different, as they suggested IRF7 to be the central transcription factor involved.…”
Section: Discussionsupporting
confidence: 91%
“…Human blood monocytes also sense Borrelia burgdorferi RNA via TLR8, resulting in IFN-b production (43,44). Although this finding is in agreement with our present study on S. aureus, the proposed signaling mechanisms are different, as they suggested IRF7 to be the central transcription factor involved.…”
Section: Discussionsupporting
confidence: 91%
“…Similarly, both human PBMCs and murine bone marrow-derived macrophages (BMDMs) responded to intracellular delivery of total bacterial RNA with TNF production (27)(28)(29)(30). In addition to inducing classical NF-kB-dependent cytokines, bacterial RNA has been identified as a strong trigger of IFN-a in plasmacytoid dendritic cells (pDCs) and of IFN-b in myeloid dendritic cells (mDCs) in an IRF-dependent manner (28,(30)(31)(32)(33)(34). Depending on the model system, the involvement of IRF1, IRF3, IRF5, or IRF7 has been implicated (30,31,33,35).…”
Section: Tatjana Eigenbrod and Alexander H Dalpkementioning
confidence: 99%
“…Early studies using HEK293 cells stably expressing human TLR3, TLR7, and TLR8 indicated that bacterial RNA can trigger IL-8 secretion by all three TLRs (29), and a potential contribution of TLR8 in transcriptional regulation of IFN-b production in human monocytes was suggested by Cervantes et al (31). Yet, the current evidence for a role of TLR8 or other TLRs in bacterial RNA sensing in primary human immune cells is weak or, in the case of NF-kB-dependent cytokines, still lacking.…”
Section: Tatjana Eigenbrod and Alexander H Dalpkementioning
confidence: 99%
See 2 more Smart Citations